An Artificial Intelligence System to Help the Player of Real-Time Strategy Games - Cunha, Renato L. de F.; Chaimowicz, Luiz (BRAZILIAN SYMPOSIUM ON GAMES AND DIGITAL ENTERTAINMENT, 2010)
Real Time Strategy (RTS) games pose a series of challenges to players and AI Agents due to its dynamical, distributed and multi-objective fashion. In this paper, we propose and develop an Artificial Intelligence (AI) system that helps the player during the game, giving him tactical and strategical tips about the best actions to be taken according to the current game state with the objective of improving the player's performance. We describe the main features of the system, its implementation and perform experiments using a real game to evaluate its effectiveness.